2004
DOI: 10.1348/000712604322779460
|View full text |Cite
|
Sign up to set email alerts
|

Working memory components of the Corsi blocks task

Abstract: A computerized version of the Corsi blocks task (Milner, 1971) was assessed for standard forward-recall order (Experiments 1 and 3) and for reversed-recall order (Experiments 2 and 3) either in a single-task or in a dual-task design combined with articulatory suppression, matrix-tapping, random-interval generation or fixed-interval generation as concurrent tasks during the encoding stage. Concurrent performance of the matrix-tapping task impaired memory performance for short as well as for longer block sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
231
2
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(266 citation statements)
references
References 38 publications
21
231
2
12
Order By: Relevance
“…The Corsi task is administered in a one-on-one setting between an administrator and participant, using blocks specifically made for this task, while our task was made to run on any computer able to run Java scripts, which are widely used. This computerization of the memory tasks facilitates a less labor-intensive administration of the task (Cornoldi & Mammarella, 2008;Rowe et al, 2009;Vandierendonck et al, 2004). This different form of task administration has been shown to result in memory spans and error rates that are similar to the physical administration of the Corsi block-tapping task (Brunetti et al, 2014) as well as for a variation of this task (Kessels et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Corsi task is administered in a one-on-one setting between an administrator and participant, using blocks specifically made for this task, while our task was made to run on any computer able to run Java scripts, which are widely used. This computerization of the memory tasks facilitates a less labor-intensive administration of the task (Cornoldi & Mammarella, 2008;Rowe et al, 2009;Vandierendonck et al, 2004). This different form of task administration has been shown to result in memory spans and error rates that are similar to the physical administration of the Corsi block-tapping task (Brunetti et al, 2014) as well as for a variation of this task (Kessels et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Computerized versions of visuospatial memory tasks advantageously facilitate group administration. These have been used before (Cornoldi & Mammarella, 2008;Kessels, de Haan, Kappelle, & Postma, 2002;Rowe et al, 2009;Vandierendonck, Kemps, Fastame, & Szmalec, 2004) and have been shown to provide memory span and error rates that are essentially analogous to those obtained using the physical version of the Corsi test (Brunetti, Del Gatto, & Delogu, 2014). We also increased the number of trials, providing a possibility for a finer scale of memory span measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Physical and computerized variants of this task have been frequently used to assess spatial WM processing and capacity (e.g. De Renzi, 1982;Burke, Allen, & Gonzalez, 2012), with studies suggesting a dissociation from verbal (Vandierendonck et al, 2004) and visual WM (Della Sala, Gray, Baddeley, Allamano, & Wilson, 1999) and a role for executive function, particularly for longer sequences (Vandierendonck et al, 2004). Due to recollection of a negatively valenced ABM possibly eliciting more vivid visual imagery, and/or leading to attentional capture and thus loading on executive resources, we predicted that this condition would reveal less accurate performance on the subsequent visuospatial WM task, relative to the neutral recollection condition.…”
Section: Methodsmentioning
confidence: 99%
“…Baddeley et al (1998), for example, found that the deviation of randomness in generated key presses increased when an irrelevant memory load was larger, which shows that maintaining a memory load may interfere with cognitive control processes needed for the generation task. Several studies have also reported poorer recall on a memory task when an unrelated random generation task was performed concurrently (e.g., Fisk & Sharp, 2003;Macizo, Bajo, & Soriano, 2006;Towse & Cheshire, 2007;Vandierendonck, 2000aVandierendonck, , 2000bVandierendonck, De Vooght, & Van der Goten, 1998a, 1998bVandierendonck, Kemps, Fastame, & Szmalec, 2004), suggesting that random generation interferes with maintenance of unrelated memory contents. Based on these findings, the expectation may be formulated that performing VTS under a memory load could result in the usage of shorter chains.…”
Section: Avenues For Further Researchmentioning
confidence: 99%